Development of automation system of the process of electromagnetic treatment of industrial wastewater from ferromagnetic impurities - Safonyk, Andrii; Burduk, Anna; Hrytsiuk, Ivanna; Pasichnyk, Vasyl (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
A mathematical model of the iron removal process taking into account the factors influencing the quality of cleaning was presented. Based on the mathematical model, a control algorithm was developed, which became the basis of the structural control scheme. Further, was set up the graphical screen for automatic and manual control, display errors and main parameters of information technology projects.